701. Blood Stream Infection And Risk Of Endocarditis Following Cardiac Valve Repair: A Population-Based Study. (31st December 2020) - McHugh, Jack; Khawaja, Talha; Baddour, Larry M; Baddour, Larry M; Crestanello, Juan; Arghami, Arman; DeSimone, Daniel; Sauver, Jennifer St
Abstract: Background: Bloodstream infections (BSIs) confer an increased risk of infective endocarditis (IE) in patients with a prosthetic cardiac valve. This relationship is less well established in patients undergoing valve repair. We conducted a retrospective population-based study to determine the incidence of BSIs following valve repair and identify risk factors associated with the development of IE. Methods: The Rochester Epidemiology Project (REP) data linkage system was used to identify all persons who underwent valve repair in a 7-county region in Southeastern Minnesota between January 1, 2010 and December 31, 2018. Medical records were screened for the development of a BSI from time of procedure until May 15, 2020. Patients were classified as having BSI only, BSI with IE at outset, or BSI with subsequent development of new IE. IE at outset was defined as cases where IE was diagnosed at the time of initial positive blood culture. Results: A total of 387 patients underwent valve repair surgery. A total of 31 (8%) patients subsequently developed a BSI, 4% within one year of surgery. Seventeen patients underwent mitral repair with annuloplasty, 9 underwent tricuspid annuloplasty, and 5 had concurrent repairs. Median time to the development of BSI was 338 days. Of the 31 patients with BSI, 4 (13%) had BSI with IE at outset. No patients developed IE subsequent to BSI, Enterococcus spp. was responsible for 3 cases of IE, and MSSA for 1. All cases occurred within one year of surgery. Given the low incidence, statistical analysis of associated risk factors for IE was not feasible. All patients with BSI and IE at outset, however, died by the end of the study period, versus 11/27 in the BSI only group. Conclusion: Incidence of BSIs was higher in patients undergoing cardiac valve repair than in the general population. The incidence of IE with a BSI was 13%, which is lower than what has been previously published. It is notable that all cases of IE occurred within one year of surgery. Recognizing that endothelialization of device surfaces occurs, it is tempting to speculate that the risk of IE may be time dependent and may decline over time. Subsequent investigation of this theory is underway. Disclosures: Larry M. Baddour, MD, Boston Scientific (Consultant)